2022
DOI: 10.1016/j.janxdis.2021.102512
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of the COVID-19 pandemic through the lens of the network approach to psychopathology: Analysis of the Brazilian Longitudinal Study of Health (ELSA-Brasil) cohort over a 12-year timespan

Abstract: Cohort studies have displayed mixed findings on changes in mental symptoms severity in 2020, when the COVID-19 pandemic outbreak started. Network approaches can provide additional insights by analyzing the connectivity of such symptoms. We assessed the network structure of mental symptoms in the Brazilian Longitudinal Study of Health (ELSA-Brasil) in 3 waves: 2008-2010, 2017-2019, and 2020, and hypothesized that the 2020 network would present connectivity changes. We used the Clinical Interview Scheduled-Revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
2
5
0
2
Order By: Relevance
“…Although we focused on the GAD-7 to align with prior research on the network structure of anxiety symptoms during the COVID crisis (i.e., Hoffart et al, 2021;Wang et al, 2020), one may want to ensure that the key role of excessive worrying would thus also appear with other measurements tools. Reassuringly, recent research has confirmed this observation and bolsters our confidence that one can generalize from our findings (e.g., Suen et al, 2021;Taylor et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Although we focused on the GAD-7 to align with prior research on the network structure of anxiety symptoms during the COVID crisis (i.e., Hoffart et al, 2021;Wang et al, 2020), one may want to ensure that the key role of excessive worrying would thus also appear with other measurements tools. Reassuringly, recent research has confirmed this observation and bolsters our confidence that one can generalize from our findings (e.g., Suen et al, 2021;Taylor et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…In Japan, in children and adolescents under 20 during the closure of schools in the first wave of the pandemic, no excess suicides were reported (Isumi et al, 2020). The authors suggested that the negative effects (fears about the pandemic, family economic difficulties, limited access to basic health facilities, and reduced social contacts) and the positive effects of the epidemic (greater time with family, increased social cohesion, decreased academic fees, and problems with peers in school) on suicides would be nullified (Suen et al, 2022). In the case of Brazil, it is possible that the 19% decrease in the number of suicides between those of 10 to 29 years of age was influenced by the possible predominance of positive pandemic effects on their incidence in relation to negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we only assessed IU through self-reported items, and did not include concurrent behavioral measurements of IU (for a discussion, see Bottesi et al, 2019;Hale et al, 2016). Third, this study was conducted during the COV-19 pandemic, characterized by great levels of uncertainty and an increased prevalence of major depressive disorder and anxiety disorders (e.g., Suen et al, 2022;Huang & Zhao, 2020;Santomauro et al, 2021;Wang et al, 2020). We cannot exclude a potential overestimation of the global prevalence of IU in the present study.…”
Section: Discussionmentioning
confidence: 99%